Systematic Review of the STEAM-Integrated 5E Learning Cycle Model to Improve Concept Mastery and Creative Thinking in Science Learning for Students - Barinta Nur Respasari; Joni Rokhmat; Imam Bachtiar; Susilawati Susilawati; Gunawan Gunawan (Balai Publikasi Indonesia, 2025)
This study aims to examine the development trend of science e-modules based on the 5E learning cycle model integrated with STEAM, reviewed from the aspects of concept mastery and creative thinking skills, to improve junior high school students' learning outcomes. This approach is relevant in facing the challenges of education in the era of globalization and the industrial revolution 4.0, which requires students to have critical and creative thinking skills. Research data were collected through bibliometric analysis of 1,000 documents indexed by Google Scholar in the period 2015–2024. The results of the analysis show that the research trend has increased significantly since 2020, with a dominance of publications in the form of articles and edited books. The main keywords that are often used include technology, student, and science learning. The application of the 5E model integrated with STEAM is not only effective in improving concept mastery but can also motivate students through digital-based learning. This study provides a foundation for the development of more innovative and relevant learning resources, and supports the implementation of technology-based learning strategies in the classroom